In search of fluctuations: Another look at China's incredibly stable GDP growth - Eeva Kerola (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
China's official real GDP growth has held surprisingly stable in recent years. As national GDP figures influence both policy analysis and political decisions, the GDP growth rate of the massive Chinese economy has also great international implications. Taking the nominal GDP growth and price index data as given and experimenting with alternative deflators, this paper attempts to track missing fluctuations in real GDP growth in recent years. Based on the constructed growth series, real GDP growth decreased during 2015–2016 and picked up in 2017. Growth has been again decelerating this year. Furthermore, the constructed growth rate seems to be well below the recent official figures.
URN:NBN:fi:bof-201901021000
Keywords: C38; E01; E3; P2; 330